Dampak Perubahan Status Taman Nasional Gunung Maras Terhadap Keadaan Sosial Ekonomi Masyarakat Desa Berbura - Asriani; Andrawati; Waliston Johannes (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The national park is a natural ecosystem reserve, managed by a zoning system for research, science, education, planting, tourism, and recreational purposes. Changing the status of mountains to national parks is a form of mountain conservation, becoming a sustainability of protected areas, and can be passed on from one generation to the next. Changes in the status of Mount Maras in Bangka Regency, Riausilip sub-district, precisely in Berbura Village, turned out to have an impact on changes in some Berbura village communities both in terms of economic and social. The purpose of this study is nothing more than to know what changes in the status of mount maras national park will do to the social life of local communities and to know what changes in the status of mount maras national park will mean for local people. The method used in this study is a kind of qualitative study using observation and descriptive study methods. The result of this study is that the social life of the people around mount maras has not changed very much. Similarly, the economic circumstances of society did not undergo a significant change either before or after the change in status of mount maras became a national park.